The surgical intervention of thoracic aortic aneurysm among octogenarians and over: A Single center study - Furui, Masato; Sakaguchi, Shoji; Akhtar, Kunwar Muhammad Aqeel; Muhammad Imran; Kakii, Bunpachi; Uchino, Gaku; Asanuma, Mai; Yoshida, Takeshi (International Journal of Endorsing Health Science Research, 2020)
Background: Thoracic endovascular aortic repair (TEVAR) is a minimally invasive procedure to repair the major blood vessel in the body i.e. aorta. This minimally invasive approach is considered as a better option in comparison to the open-heart surgery by among octogenarians. Therefore, the aim of this study was to examine the trends of postoperative complications among octogenarians and nonagenarians with arch, descending, or thoracoabdominal aortic aneurysms. Methodology: This interventional, single center study initially included a total of 329 consecutive patients with arch, descending, or thoracoabdominal aortic aneurysms. The study was conducted at Matsubara Tokushukai Hospital, Japan between May 2005 to November 2018. Of the total, 129 patients met the inclusion criteria and were enrolled. 32 patients were excluded as they didn’t provide consent for the surgical intervention and preferred conservative medical treatment only. While the remaining 97 patients had operative indications, 64 of these were treated with TEVAR (SG group) and 33 were treated with open surgery (OS group). Early and late outcomes and the relation with bedridden status were examined retrospectively. Data was analyzed using JMP 9.0 software (SAS Institute, Inc., Cary, NC). Results: Among the enrolled patients 49.5% were males and 50.5% were females. Decreased complications were observed among the patients of SG group as compared to the OS group. The highest mortality 69% was noted among the group treated with medical therapy alone with the confidence of interval of 95%. Furthermore, most of the patients in the OS group developed a complication of cerebral infarction and also needed tracheotomy during long-term hospital stay. Moreover, deaths occurring in bedridden patients were more common in the OS group than the SG group respectively. Conclusion: It is concluded that SG is a better therapeutic approach as compared to the OS and the conservative therapy alone.